Altered GABAA receptor function in women with endometriosis: a possible pain‐related mechanism - Sandström, Anton; Bixo, Marie; Bäckström, Torbjörn; Möller, Anna; Turkmen, Sahruh (Acta obstetricia et gynecologica Scandinavica, 2023)
Introduction The mechanism underlying endometriosis‐related pain remains poorly understood. Previous studies have indicated that γ‐aminobutyric acid (GABA) type A (GABAA) receptors and GABAergic substances (eg endogenous neurosteroids) play important mechanistic roles in various pain conditions. Our primary objective was to compare GABAA receptor function between women with endometriosis and healthy controls by performing a challenge test with diazepam, a GABAA receptor agonist, using the saccadic eye velocity as the main outcome. The secondary objective was to investigate the relation between GABAA receptor function and serum levels of allopregnanolone, an endogenous positive modulator of the GABAA receptor, in the participating women. Material and methods 15 women with pelvic pain and laparoscopically confirmed endometriosis and 10 healthy, symptom‐free, control women, aged 18–40 years, underwent the diazepam challenge test during the follicular phase of the menstrual cycle. Basal serum allopregnanolone levels were measured prior to diazepam injection. Results Compared with healthy controls, women with pelvic pain and confirmed endometriosis had a significantly smaller change in saccadic eye velocity after GABAA receptor stimulation with diazepam, indicating lower sensitivity to diazepam. The saccadic eye velocity response was not correlated with the serum allopregnanolone levels. Conclusions Women with painful endometriosis show altered GABAA receptor function, depicted as a muted response to an exogenous GABAA receptor agonist. Women with endometriosis show a significantly decreased GABAA receptor‐mediated inhibition compared with healthy controls, indicating changes in the central nervous system that could explain why treatment targeted at the nociceptive component of the pain sometimes fails in these women.